A Plant-Centered Diet and Onset of Chronic Kidney Disease in 20 Years of Follow-Up: Findings from the Coronary Artery Risk Development in Young Adults (CARDIA) Cohort. (29th May 2020) - Choi, Yuni; Jacobs, David; Chu, Haitao; Duprez, Daniel; Gallaher, Daniel; Larson, Nicole; Shikany, James; Schreiner, Pamela; Shroff , Gautam; Steffen, Lyn
Abstract: Objectives: Chronic kidney disease (CKD) is an increasing health problem in young adults and may be associated with dietary patterns. We examined the association of a plant-centered diet with incident moderate-to-very high risk CKD in young adults who were initially free of CKD. Methods: We followed 3026 community-based participants (Black and White men and women) from the Coronary Artery Risk Development in Young Adults (CARDIA) cohort (1985–86 to 2015–16). Diet was assessed by an interviewer-administered diet history at exam years (Y) 0, 7, and 20. Higher plant-centered diet quality was judged by higher cumulative average value of the A Priori Diet Quality Score (APDQS, range 0–132), a hypothesis-driven index based on 46 food groups. A higher APDQS is characterized by high consumption of nutritionally rich plant foods and limited meat, added sugars, and other less nutritious foods. Kidney status, assessed at 5-year intervals from Y10 to Y30, was based on estimated glomerular filtration rate (eGFR) using CKD-EPI creatinine equation and spot urine albumin-to-creatinine ratio (ACR). CKD diagnosis included new onset of micro- or macro-albuminuria (ACR ≥30 mg/g), eGFR <60 mL/min/1.73m, 2, or (hospitalized or fatal) end stage renal disease. Prevalent CKD cases throughout Y10 were excluded. Proportional hazards regression estimated the association of time-varying cumulative average APDQS with incident CKD, adjusted for age, sex, race, education, energy intake, % energy from protein, physical activity, and smoking. Results: Mean Y10 age was 35.1 y (±3.6 y) and mean cumulative average APDQS was 65.0 (±11.4). We identified 358 incident CKD cases (59 of whom were severe cases) during mean follow-up of 17.7 years (±4.4) after Y10. Eating a plant-centered, high quality diet was associated with a lower risk of incident CKD. In multivariable analysis, participants in the highest quintile of the APDQS had 37% (95% confidence interval: 0.41–0.97) lower risk of CKD as compared with those in the lowest quintile of the APDQS. For each 11-point increment in APDQS, there was 15% lower risk of CKD (0.74–0.97). The association remained similar after further adjustment for prevalent cases of hypertension and diabetes. Conclusions: A plant-centered, high quality diet was associated with a lower risk of developing CKD. Funding Sources: CARDIA and MnDRIVE (University of Minnesota).